Landfill methane oxidation using biocover under laboratory conditions / Siti Aishah Kamarul Baharain - Siti Aishah, Kamarul Baharain (2011)
Generation of waste continues to increase in response to rapid population growth. An estimated 10 million tonnes of total waste was produced in 2008 in Malaysia which was sent to 260 landfills. Malaysian landfills produce 1.3-7.5 L/kg/year of methane gas. Landfill gas consists mainly of methane (55%). CH4 is recognized as the primary global warming contributor with CH4 being 25 times more infrared absorptive capacity than CO2. Using “Biocover” at landfills is one option for methane oxidation. Objective of this study is to analyze the physical and chemical characteristic of the Biocover material (garden waste compost and black soil) in order to propose suitable landfill covers for methane oxidation under tropical conditions. Batch incubation experiments using Wheaton bottles showed that garden waste compost was the best Biocover material because it took only 4 days for complete methane oxidation compared to black soil, which took 7 days. Meanwhile Wheaton bottle experiments using 3 different parameters (temperature, moisture content and pH) also demonstrated that compost was still the best material for Biocover. In addition to that, the optimum conditions for both Biocover materials used in this study was at 35°C, with 60% moisture content and pH 6. Biocover Performance Index (BPI) obtained for compost (2.08 × 10 -3 μgg-1h-1) was higher than that for black soil (1.19 × 10 -3 μgg-1h-1). Meanwhile the Rp (potential oxidation rate) value for compost (17.036 mL/d) was almost double the value for black soil (10.806 mL/d). This clearly indicates that garden waste compost was the most effective and suitable Biocover material for methane oxidation under tropical conditions.